2010
DOI: 10.1159/000318879
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Vowel Productions in Prelingually Deaf Children Using Cochlear Implants, Severe Hearing-Impaired Children Using Conventional Hearing Aids and Normal-Hearing Children

Abstract: Objective: The purpose of this study was to compare vowel productions by deaf cochlear implant (CI) children, hearing-impaired hearing aid (HA) children and normal-hearing (NH) children. Patients and Methods: 73 children [mean age: 9;14 years (years;months)] participated: 40 deaf CI children, 34 moderately to profoundly hearing-impaired HA children and 42 NH children. For the 3 corner vowels [a], [i] and [u], F1, F2 and the intrasubject SD were measured using the Praat software. Spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…The more complicated 'indirect' hypothesis is that the improved nasalance is an indirect consequence of changes in other speech production parameters. Indeed, previous studies of Baudonck et al [1][2][3] describe improved speech production characteristics in CI children compared to HA children. The consonant production of implanted children is more adequate than the consonant production of HA 70 dBHL children, the voices of the CI children are perceptually judged to be better compared to HA 70 dBHL and HA children show the tendency to a more dorsal articulation of the vowels, which was not seen in the CI children.…”
Section: N Baudonck Et Al / International Journal Of Pediatric Otormentioning
confidence: 95%
See 2 more Smart Citations
“…The more complicated 'indirect' hypothesis is that the improved nasalance is an indirect consequence of changes in other speech production parameters. Indeed, previous studies of Baudonck et al [1][2][3] describe improved speech production characteristics in CI children compared to HA children. The consonant production of implanted children is more adequate than the consonant production of HA 70 dBHL children, the voices of the CI children are perceptually judged to be better compared to HA 70 dBHL and HA children show the tendency to a more dorsal articulation of the vowels, which was not seen in the CI children.…”
Section: N Baudonck Et Al / International Journal Of Pediatric Otormentioning
confidence: 95%
“…Even though these implants primarily facilitate speech perception, they are also an important aid in the development of several speech production skills, such as overall intelligibility [14][15][16], the production of vowels [2] and consonants [1]. The few studies which focused on resonance characteristics in children using CI [17][18][19][20][21] reported contradictory findings concerning several aspects of nasality or nasalance and conclusions were based on small sample sizes.…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, in previous studies of Baudonck et al [4,[15][16], CI children still showed some abnormalities for several speech parameters including articulation of consonants and vowels and voice quality. Yet, when considering the results of the present study, those abnormalities in CI children do not appear to affect intelligibility seriously, although they were clearly perceptible.…”
Section: Discussionmentioning
confidence: 83%
“…Vowels are a critical factor for intelligibility of speech (10)(11)(12) and are involved in both prosodic and segmental features of speech (13,14). The corner vowels ("a," "i," and "u") are more important than other vowels, because they represent a wide range of production situations of the tongue (15). Persian vowels are divided to 2 groups, based on the position of the tongue (front vs. back): front vowels include "i", "e", and "ae", and back vowels include "u", "o", and "a".…”
Section: Introductionmentioning
confidence: 99%